Circumstances of Accidental Poisoning in Childhood. Issue 5625 (26th October 1968) - Jackson, R. H.; Walker, J. H.; Wynne, N. A.
Abstract : Of 377 children with accidental poisoning, the commonest ages were 1, 2, and 3. The most important contributory factor was that the poison was kept in an inappropriate place. Most containers were closed, but the children found them easy to open. In some cases the container itself was unsuitable for the contents. The frequency of poisoning in childhood might be reduced in six main ways: (1) a reduction in the quantity of drugs kept in the home; (2) the provision of drug cupboards; (3) the provision of containers that are difficult for children to open, or individually foil-wrapping tablets; (4) making tablets less attractive to children; (5) clear identification of potential poisons; and (6) increasing parental awareness of the circumstances under which poisoning occurs. A plea is made for further sociomedical research into the prevention of poisoning.